DEVELOPMENT STRATEGY OF NEW UZBEKISTAN: ISSUES OF IMPLEMENTATION AND SYSTEM FORECASTING - Karimov Diyor Mukhtarovich; Sultanova Lola Sharafovna (Journals Park Publishing, 2023)
The processes of modernization of Uzbekistan cover all spheres of society. The basis of the ongoing transformations are official documents that fix the stages and main directions of reforms. The article analyzes the problems of implementing the Development Strategy of the new Uzbekistan, associated with the shortcomings of the organization of systematic work, including in the field of urbanization and urban construction. In the implementation of plans, it is necessary to take into account force majeure circumstances, such as the COVID -19 pandemic and its consequences, and abnormal climate changes. Also, such constraining factors as poverty, inflation, and some problematic aspects of the introduction of the digital economy remain. It is important to solve these problems on a systemic basis and for the long term, rather than reacting to the consequences. This is the only way to ensure the fulfillment of the tasks set in the Strategy for the Development of the New Uzbekistan.
Keywords: Development strategy of new Uzbekistan, economy, development, Uzbekistan, urbanization, pandemic, infrastructure, problems, state, policy, solution, implementation.